2017
DOI: 10.1017/s0031182017002256
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for trophic transfer ofInodosporus octosporaandOvipleistophora arlon. sp. (Microsporidia) between crustacean and fish hosts

Abstract: Within aquatic habitats, the hyper-abundant Order Crustacea appear to be the predominant host group for members of the Phylum Microsporidia. The musculature, a common site of infection, provides access to biochemical (carbohydrate-rich) and physiological (mitochondria-rich) conditions conducive to prolific parasite replication and maturation. The significant proportion of body plan devoted to skeletal musculature in Crustacea provides the location for a highly efficient intracellular parasite factory. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Also, even if relatively scarce, investigations in aquatic organisms other than amphipods or fish led to the discovery of several new microsporidian species, but not Dictyocoela (e.g. for the most recent [63][64][65][66][67][68][69][70]), contrasting with the studies made on amphipods of different clades where Dictyocoela were easily found (e.g. for the most recent [19,[26][27][28]38].…”
Section: Discussionmentioning
confidence: 95%
“…Also, even if relatively scarce, investigations in aquatic organisms other than amphipods or fish led to the discovery of several new microsporidian species, but not Dictyocoela (e.g. for the most recent [63][64][65][66][67][68][69][70]), contrasting with the studies made on amphipods of different clades where Dictyocoela were easily found (e.g. for the most recent [19,[26][27][28]38].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, microsporidia infect silkworms, bees, salmon, shrimp, and other economically important and farmed animals (Lom and Nilsen, 2003;Wang et al, 2006;Klee et al, 2007;Sokolova et al, 2015), and have caused significant economic losses to the agriculture and aquaculture industries (Stentiford et al, 2016). More than 63 genera have been reported infecting crustaceans (Bojko et al, 2020), of which at least 15, including Agmasoma, Ameson, Apotaspora, Enterocytozoon, Inodosporus, Myospora, Ovipleistophora, Paradoxium, Perezia, Pleistophora, Potaspora, Thelohania, Triwangia, Tuzetia, and Vavraia have been identified in shrimp (Wang et al, 2013;Stentiford et al, 2015;Ding et al, 2016;Sokolova and Overstreet, 2018;Stentiford et al, 2018). Microsporidia infections within economically important crustaceans can lead to slow growth, muscle turbidity, hepatopancreatic lesions, and loss of economic value-all of which can seriously endanger the crustacean aquaculture industry (Tourtip et al, 2009;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…What would be the consequences of this infection for king crab fisheries? In the Northern Hemisphere, a sharp decline in crab abundance has been observed in the last years due to microsporidian infections [4,14], notably affecting the economic activity [18,19]. In the Magellan region, L. santolla supports the most important fishery and their exports have increased over the years, reaching US$52 million in 2016 [42].…”
Section: Potential Economic Impact Of Microsporidiosis In King Crabmentioning
confidence: 99%
“…Pathogenic parasites can imperil diverse commercial activities, ranging from honeybee culture to fish and crustacean fisheries [1,2]. In recently described pathogenic parasites [3,4], the understanding of the pattern of infection is a mandatory first step to develop powerful predictive models. Considering that host attributes like sex and size may significantly influence the probability of infection of parasites [5,6], the assessment of the pathogenic potential of these species should include the associations (or lack thereof ) between prevalence, host sex and host size.…”
Section: Introductionmentioning
confidence: 99%